2015
DOI: 10.1189/jlb.1ab1014-488rr
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Ly6G antibodies determine macrophage phagocytosis of neutrophils and alter the retrieval of neutrophils in mice

Abstract: Fluorescently labeled Ly6G antibodies enable the tracking of neutrophils in mice, whereas purified anti-Ly6G rapidly depletes neutrophils from the circulation. The mechanisms underlying neutrophil depletion are still under debate. Here, we examined how identical Ly6G antibodies coupled to different fluorochromes affect neutrophil fate in vivo. BM cells stained with Ly6G antibodies were injected into mice. The number of retrieved anti-Ly6G-FITC(+) cells was reduced significantly in comparison with anti-Ly6G-APC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…This outcome is in conflict with findings of others who observed that following co-injection of Ly6G (Gr1)-APC-labeled “aged” neutrophils and Ly6G (Gr1)-FITC-labeled “young” neutrophils, the APC-labeled “aged” neutrophil population dominated in the BM of the recipients [26]. We have previously shown that coupled fluorochromes can alter the functional properties of neutrophil-targeting Ly6G antibodies [25] and assume that the conflicting results might be explained by the cell-depleting effect of the FITC-coupled Ly6G antibody.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…This outcome is in conflict with findings of others who observed that following co-injection of Ly6G (Gr1)-APC-labeled “aged” neutrophils and Ly6G (Gr1)-FITC-labeled “young” neutrophils, the APC-labeled “aged” neutrophil population dominated in the BM of the recipients [26]. We have previously shown that coupled fluorochromes can alter the functional properties of neutrophil-targeting Ly6G antibodies [25] and assume that the conflicting results might be explained by the cell-depleting effect of the FITC-coupled Ly6G antibody.…”
Section: Resultsmentioning
confidence: 69%
“…Single cell suspensions from blood, spleen, lungs and BM were isolated as described previously [22, 24, 25, 26]. Leukocytes from single cell suspensions were prepared by lysis of red blood cells in ACK buffer (0.155 M NH 4 Cl, 0.01 M KHCO 3 , 0.1 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to occur through a density feedback mechanism that detects cell loss, yet the sensors of this cell loss have not been elucidated [81]. Notably, antibody-mediated neutrophil depletion, which enhances emergency granulopoiesis, requires Mϕ-dependent efferocytosis [82]. Thus, while efferocytosis suppresses granulopoiesis at steady state [24, 25, 83], this process may enhance granulopoiesis under stress conditions where rapid neutrophil turnover and clearance occur.…”
Section: Macrophages Regulate Stress-hematopoiesismentioning
confidence: 99%
“…into the mice. We used 5 μg of antibody because administration of a low dose (1 to 40 μg) of fluorochromecoupled anti-Ly-6G antibody to mice does not affect neutrophil recruitment (56), and injection with PE-conjugated antibodies does not induce antibodydependent neutrophil depletion compared with other fluorescent dyes (such as FITC) in vivo (57).…”
Section: Methodsmentioning
confidence: 99%